Kualiti pembangunan modal insan berminda kelas pertama di ILP Pasir Gudang Johor Bahru - Ibrahim, Siti Marliza (2012)
The Malaysia education system especially technical and vocational education is now entering a new era by transformations conducted. In this context, human capital produced from this system should be completed with some aspects to ensure the output of quality is assured. The purposeof this studyisto determinethe quality ofhuman capitalbased on first class minded criteria during training programat Industrial of Training Institute (ILP) Pasir Gudang, Johor Bahru. The aspectsthathave been studied are spiritual development, social leadership development, academicknowledge development and career skills. Research design used in this study is descriptive research with a total of 175 respondents. Selectedrespondentsare traineesfrom semester 3 and 4 who are enrolled in various engineering course at the certificatelevel. The instrument used isa set of questionnaire that is divided into two sections, whichisPart Aregarding the respondent’s demography and partB regardingtherespondent’s feedback to the research questions. The reliability value for the instrument isa = 0.892which is at the highest level.The result of this study has been analysed using Statistical Package for Social Science (SPSS) version 16.0 software to obtain frequency, percentage and mean.The findings of this research showthat the quality of first class minded among the trainees inILP PasirGudang isathigh levels with an average mean value 4.52. The further analysis found thatmean for spiritual development is 4.59, mean for social leadership developmentis 4.36,mean foracademic knowledge development is 4.63andmean forcareer skills development is 4.48. Inferential analysis also carried out on element of program with spiritualdevelopment, social leadership development, academic knowledge development and career skills. The finding were found, there is no significant betwee all the factors with the programmed offered by ILP. Therefore, based on this study, it is suggested to conduct this research furtherat all Malaysia’s Institute of Industrial Training (ILP) in orderto determine a holisticlevel of human capital developmentamong trainees.